(untitled) (Journal of Surgical Sciences, 2020)
Background: Pregnancy-induced hypertension constitutes a major cause of morbidity and mortality in developing nations and it complicates about 6-8% of pregnancies. Severe preeclampsia poses a dilemma for the anesthesiologist especially in emergency situations where caesarean deliveries are planned for uninvestigated or partially investigated parturients. The choice of anesthesia in preeclamptic mothers undergoing Cesarean delivery has been debated for years. General as well as regional anesthetic techniques are equally acceptable for cesarean delivery in pregnancies complicated by preeclampsia. Currently, the safety of regional anesthesia technique is well established and they can provide better obstetrical outcome. Objective: To study the outcome and elaborate the hemodynamic changes associated with spinal anesthesia in preeclampsia. Methods: The study was carried out in com ii la medical college hospital and private clinics in comilla among preeclamptic women who underwent Lower Segment Caesarean Section (LSCS) under spinal anesthesia between January 2013 and July 2017. Both emergency as well as elective cases were included in the study. Patients’ records were studied and analyzed. The drug used for spinal anesthesia was hyperbaric Bupivacaine 0.5%. Subarachnoid block was performed in either L3-L4 or L2-L3 intervertebral segment with patient sitting up. Spinal needle 25G was used. The hemodynamic response (systolic blood pressure, diastolic blood pressure, heart rate) and Sp02 were observed. Results: Total of 310 cases was included in our study. Age ranged from 17 to 37 years. The duration of surgery ranged from 25mins to 100mins. According to observation, both systolic and diastolic blood pressure dropped to minimum within the initial 10 minutes of spinal anesthesia. Heart rate fluctuation was minimal with an initial small drop within 10 minutes of spinal anesthesia. Similarly, Sp02 also showed a subtle decline within 20 minutes of spinal anesthesia. Conclusion: Our study finds spinal anesthesia as a preferred method taking into account the relatively stable and better hemodynamic stability, convenience in procedure and rapid and predictable anesthesia and no risks of sudden critical hypotension. Journal of Surgical Sciences (2018) Vol. 22 (1): 30-35